A pore-network study on the factors influencing the isothermal drying of single- and dual-scale porous media. Issue 10 (12th July 2021) - Xu, Zhenyu; Pillai, Krishna M.
Abstract: This paper analyzes a pore-network simulation to model isothermal drying in single-porosity and dual-porosity porous media after employing the invasion-percolation algorithm and the effect of liquid film. Utilizing a novel logistic equation to relate the inside and outside variables of the pore-network, the fully coupled implicit method is employed to solve the vapor transport problems in the pore-network and in the adjoining external flow field. A parametric study is conducted on the drying of a single-porosity square network placed next to a slit flow. Higher hydraulic diameter of the throats leads to higher drying rates and longer constant drying rate periods. The drying time increases and the drying rate decreases as the throat cross-section changes from a triangle to a square to a hexagon to a circle due to the weakening of the film effect. Increasing the external air humidity from 30% to 70% leads to a large decrease in the drying rates and the consequent increase in the overall drying times. Increasing the external flow velocity through Péclet number has little effect on the drying rates and times. Increasing the contact angle makes it harder for the corner films to materialize, which in turn decreases the constant drying rate period. Increase in the surface tension leads to an increase in the spread of the corner film which results in longer constant drying rate periods. Later the drying simulations of a dual-porosity domain using 100 × 100 networks are carried out in a uniform air flow after keeping either the large pores or the small pores side open. The former leads to faster drying characterized by a previously observed bi-linear drying curve, and complete emptying of the outer large pores before the inner small pores. The latter witnesses the phenomenon of capillary pumping leading to a premature emptying of the inner larger pores. The case of all side open is also studied. Changing the throat cross-section from circle to square leads to a much faster drying due to the appearance of the film. Introduction of microstructural irregularity in the network by randomly changing the throat diameter and coordination number of pores does not affect the drying rate and drying time significantly.